ANALYZING THE IMPACT OF REWARD AND EMPLOYEE DEVELOPMENT ON EMPLOYEE PERFORMANCE AT PT. BANK NEGARA INDONESIA (PERSERO) Tbk MANADO BRANCH - Pontoh, Pamela Rachel Gerhana (Sam Ratulangi University, 2016)
ABSTRACT Â The success of a company, partly seen from the employee performance of the company. Not a few companies that suffer because of the employee's performance is unsatisfactory. Good employee performance to be achieved each company by giving an award to each employee and make employee development. The purpose of this study was to determine the effect of simultaneous and partial reward, employee development to employee performance. Where researchers take the place of research at PT. Bank Negara Indonesia Persero Tbk. Manado (BNI), with a population of 30 respondents as sample and using simple random sampling method. This study uses associative and through multiple regression analysis. The results showed appreciation, employee development has a significant influence on the company's performance both simultaneously and partially. Bank BNI management is expected to pay attention, control the reward, the existing employee development in order to further improve the employee performance. Keywords: Reward, Employee Development, Employee Performance